CRIMINAL LIABILITY FOR SPREADING HOAX NEWS THROUGH ELECTRONIC MEDIA IN THE PERSPECTIVE OF LAW NUMBER 19 YEAR 2016 - Sinthiya, Ida Ayu Putu Anggie (JLCEdu (Journal of Learning and Character Education), 2022)
Advances in information and communication technology have an impact in terms of delivering information that runs so fast and can be accessed through social media such as Facebook, Twitter or mobile phone messages such as WhatsApp and others. Due to this progress, social media users cannot filter properly regarding the truth of the news that will be received or disseminated so that it gives birth to hoax news. The criminal responsibility for spreading hoax news is contained in the article referring to the provisions of Article 28 paragraph (1) 45A paragraph (1) of the Constitution of the Republic of Indonesia Number 19 of 2016. In the process of proving the crime of spreading hoaxes in online media, additional evidence is contained in Article 5 of the ITE Law concerning Electronic Information and Electronic Documents and/or printed results. Factors that influence the spread of hoaxes are curiosity, weak journalism, weak economic factors, the emergence of unofficial media, the low quality of media literacy. Prevention of hoax news by means of media literacy so that they have useful skills in processing, accessing, analyzing information and evaluating any information that is obtained or wants to be disseminated by social media. So that social media users can think critically about what they see and read so that it will give birth to a social media order that has etiquette.